Immunological Responses Triggered by Photothermal Therapy with Carbon Nanotubes in Combination with Anti‐CTLA‐4 Therapy to Inhibit Cancer Metastasis. (20th October 2014) - Wang, Chao; Xu, Ligeng; Liang, Chao; Xiang, Jian; Peng, Rui; Liu, Zhuang
<x xml:space="preserve">Abstract</x> Photothermal ablation of primary tumors with single‐walled carbon nanotubes is demonstrated to be able to trigger significant adaptive immune responses, which are not observed if tumors are removed by surgical resection. Such a treatment in combination with anti‐CTLA‐4 antibody therapy is able to prevent the development of tumor metastasis, which is a major cause of cancer death. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>